2005
DOI: 10.1051/fruits:2005032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying parameters onβ-carotene retention in mango leather

Abstract: Influence of drying parameters on β-carotene retention in mango leather. Abstract-Introduction. Dried mango slices are a common snack product in Southeast Asian countries. Mashing the carotenoid-containing mango flesh and drying the puree to mango leather is a promising alternative to utilise even over-mature or small fruits and fruits with irregular size as low-cost raw materials. Within the study, the impact of blanching and air temperature (40-90°C) on drying time and quality was investigated. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Better retention of carotenoid was observed in samples packed in BOPP. Loss of carotenoids content during storage could be due to non-oxidative changes (cis-trans isomerization, epoxide formation of thermal degradation) or oxidative changes [21]. Improved retention of carotenoids content in fruit leather might be due to protective action of SO 2 [22].…”
Section: Effect Of Different Blending Ratio On the Yield Of Blended Guava And Papaya Fruit Leathermentioning
confidence: 99%
“…Better retention of carotenoid was observed in samples packed in BOPP. Loss of carotenoids content during storage could be due to non-oxidative changes (cis-trans isomerization, epoxide formation of thermal degradation) or oxidative changes [21]. Improved retention of carotenoids content in fruit leather might be due to protective action of SO 2 [22].…”
Section: Effect Of Different Blending Ratio On the Yield Of Blended Guava And Papaya Fruit Leathermentioning
confidence: 99%
“…Yapılan bir diğer çalışmada ise dut pestilinde toplam fenolik bileşik miktarı, gallik asit eşdeğerinde 4.79 mg/ g, erik pestilinde 28.36 mg/g olarak, antioksidan aktivite oranları ise dut pestilinde %40.05 ve erik pestilinde %90.92 olarak bulunmuştur [25]. Mango pestili üzerine yapılan bir çalışmada ise 80°C'de kurutma ile elde edilen pestilde, meyve püresindeki β-karoten miktarının %75'i kadar β-karoten bulunurken, 90°C'de kurutma sonucu ise %35'den azı korunabilmiştir [26]. Meyvelerin fenolik bileşikler, karotenoitler gibi sağlık açısından faydalı özelliklere sahip biyoaktif bileşenlerce zengin olduğu bilinmektedir [27].…”
Section: Pesti̇li̇n Ki̇myasal Bi̇leşi̇mi̇ Ve Besi̇n Değeri̇unclassified
“…Many experimental studies have proven that hot air drying of fruit is significantly influenced by the drying temperature and air velocity, whereas the specific humidity did not have a major impact on the drying rate [8,11,16,17]. Furthermore, many researchers have extensively documented the influence of these drying conditions on quality attributes such as color, texture, total soluble solids (TSS), starch, sugar, moisture content, fibers, phenolic contents, vitamins, and antioxidants of the dried mango [9,[18][19][20][21][22][23][24]. In most of these studies, it was well observed that drying at temperatures of 70 • C and 80 • C contributed to rapid degradation of the fruit's nutritional components, whereas this loss was greatly reduced at temperatures of 40 • C to 60 • C. Although the effects of different drying conditions on product quality are well studied, there is still a lack of information related to enzymatic activity retention, particularly in the varieties Sindri, Samar Bahisht Chaunsa, and Tommy Atkins.…”
Section: Introductionmentioning
confidence: 99%